Unfair dismissal, its burden of proof, and resulting effects under Algerian Legislation - Salah, Chorfi (The International tax journal, 2026)
This academic study examines unfair dismissal (disciplinary and arbitrary termination) under Algerian labor legislation, focusing primarily on Article 73 of Law No. 90-11 of April 21, 1990, as amended and supplemented by Law No. 91-29 of December 21, 1991. It analyzes the concept of unfair dismissal, the exhaustive list of serious faults justifying disciplinary termination, the burden of proof (which generally rests on the worker to disprove the employer's stated reasons after disclosure), and the legal effects of unfair termination. These effects include, as primary remedies, either reinstatement with retention of acquired privileges or, in case of refusal by either party, financial compensation of no less than six months' wages, without prejudice to additional damages for harm suffered. The study highlights persistent doctrinal and judicial inconsistencies in the application of Article 73 due to its ambiguity, reviews relevant Supreme Court jurisprudence, and concludes by calling for a clearer legislative amendment while affirming the Supreme Court's central role in unifying interpretation pending such reform.